Highly conductive corrosion-resistant composite bipolar plate and method of making same

CN122992002APending Publication Date: 2026-10-27QUANZHOU KAIYING POWER SUPPLY ELECTRICAL APPLIANCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611476660.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

针对现有技术的不足,本发明提供了一种高导电耐腐蚀复合材料双极板及其制备方法,解决了现有双极板导电性能、耐腐蚀性能、机械性能及使用寿命难以兼顾的问题

Benefits of technology

(1)本发明采用改性氧化铝晶须复合增强材料作为双极板增强组分。氧化铝晶须具有优良的耐热性和力学强度,可作为增强骨架,提高复合材料的机械性能和结构稳定性。首先利用盐酸溶液调节体系至酸性将氧化铝晶须表面的羟基充分质子化,提高晶须表面的反应活性。将钛酸四丁酯引入活化氧化铝晶须分散体系中,在醇溶液环境下发生水解缩合反应,生成的二氧化钛组分均匀负载于氧化铝晶须表面,形成二氧化钛修饰氧化铝晶须,为后续碳化反应提供均匀分布的钛源,同时可提高氧化铝晶须表面的活性位点数量,使碳化钛结构能够在晶须表面原位形成,增强界面结合强度,避免外加增强体常见的团聚与弱粘结问题。再进行高温碳化处理,在还原性气氛作用下,二氧化钛逐步转化形成碳化钛结构,使氧化铝晶须表面构建具有导电性的碳化钛修饰层。其中,碳化钛具有较高的电导率、耐腐蚀性及高热稳定性,可改善氧化铝晶须表面的电荷传输能力,提高增强材料的导电性能,同时,碳化钛修饰层的引入能够增加晶须与导电填料之间的界面接触机会,有利于复合材料内部导电通路的构建。甲烷气体作为碳源,H2能够调节甲烷裂解速率并抑制无定形碳过度沉积,Ar作为稀释气体,调节反应气氛中反应物分压,有利于碳化钛均匀沉积。随后采用γ-缩水甘油醚氧丙基三甲氧基硅烷对碳化钛修饰氧化铝晶须进行表面处理,在晶须表面形成有机硅烷连接层,同时,γ-缩水甘油醚氧丙基三甲氧基硅烷中的有机官能团能够提高增强材料与聚苯硫醚树脂之间的界面结合能力,降低晶须团聚现象。将经表面改性的碳化钛修饰氧化铝晶须与聚苯硫醚进行熔融共混,使聚苯硫醚均匀包覆于增强材料表面,形成具有良好分散性和界面结合能力的改性氧化铝晶须复合增强材料。该增强材料加入双极板体系后,可通过氧化铝晶须增强、碳化钛导电、硅烷界面调控及聚苯硫醚化学稳定的协同作用,提高双极板的机械强度、导电性能及长期耐腐蚀稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of bipolar lead storage batteries, and particularly discloses a high-conductivity corrosion-resistant composite material bipolar plate and a preparation method thereof. The composite material bipolar plate takes natural flake graphite, carbon black and polyphenylene sulfide resin as the basis, introduces modified alumina whisker composite reinforcing materials, improves the mechanical properties, the conductivity and the interface stability of the bipolar plate, coats a modified polyaniline conductive corrosion-resistant coating on the surface of the composite bipolar substrate, constructs a continuous electron transmission path by using a conjugated conductive structure, and enhances the corrosion resistance in an acidic environment by using a nitrogen and sulfur heterocyclic structure. Then, positive and negative lead paste active layers are prepared on the two sides of the bipolar substrate, and the composite material bipolar plate for the bipolar lead storage battery is formed. The bipolar plate prepared by the application has the advantages of excellent conductivity, good corrosion resistance, high mechanical strength and excellent long-term service stability, and can meet the application requirements in a complex electrochemical environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bipolar lead-acid battery technology, specifically a highly conductive and corrosion-resistant composite material bipolar plate and its preparation method. Background Technology

[0002] Currently, bipolar plates are mainly classified into three categories: graphite bipolar plates, metallic bipolar plates, and composite material bipolar plates. Graphite bipolar plates possess excellent conductivity and corrosion resistance, but their inherent brittleness and poor mechanical properties limit their large-scale application. While metallic bipolar plates exhibit excellent conductivity and mechanical strength, they are susceptible to corrosion in acidic operating environments, and their anti-corrosion coatings are prone to peeling and failure, leading to reduced battery output efficiency. Composite material bipolar plates, with their advantages of adjustable performance and controllable cost, have become a key research focus in the field of bipolar plates.

[0003] Chinese patent application CN115566202A discloses a novel metal-graphite composite bipolar plate and its preparation method. This method combines the advantages of metal bipolar plates and composite bipolar plates, using a metal plate as the backing plate for graphite, which effectively avoids cracking at the thinnest point and solves the problem of difficulty in forming the thinnest part of the bipolar plate. However, the interfacial bonding between the metal and graphite still needs further attention. Chinese patent application CN103633340A discloses a modified expanded graphite-based composite material bipolar plate and its preparation method. This bipolar plate is composed of expanded graphite, thermoplastic phenolic resin, and carbon aerogel, and has advantages such as good electrical conductivity, low bulk density, good mechanical properties, good wetting properties, and good thermal stability. However, the stability of this material in long-term acidic environments needs to be verified.

[0004] Therefore, there is an urgent need to develop a highly conductive and corrosion-resistant composite bipolar plate that combines excellent conductivity, corrosion resistance, mechanical strength, and service life. Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a highly conductive and corrosion-resistant composite material bipolar plate and its preparation method, solving the problem that existing bipolar plates cannot simultaneously achieve good conductivity, corrosion resistance, mechanical properties, and service life.

[0006] (II) Technical Solution To achieve the above objectives, this invention discloses a highly conductive and corrosion-resistant composite material bipolar plate, the preparation method of which includes the following steps: Step 1: Natural flake graphite, carbon black, polyphenylene sulfide resin, modified alumina whisker composite reinforcing material, antioxidant, polyphenylene sulfide grafted maleic anhydride, and dispersant are added to a mixer for mixing. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain composite substrate granules. The composite substrate granules are placed in a mold, hot-pressed, and demolded to obtain a composite bipolar substrate. Step 2: Add the modified polyaniline conductive material to N-methylpyrrolidone, ultrasonically disperse for 20-40 minutes, then add the binder and mix evenly to obtain a conductive and anti-corrosion slurry. Coat the conductive and anti-corrosion slurry evenly on both sides of the composite bipolar substrate and dry to obtain the modified composite bipolar substrate. Step 3: Apply positive lead paste to one side of the modified composite bipolar substrate and negative lead paste to the other side of the modified composite bipolar substrate. After impregnation with sulfuric acid solution, place the substrate in a constant temperature and humidity chamber for curing to obtain a highly conductive and corrosion-resistant composite material bipolar plate.

[0007] Preferably, the natural flake graphite in step one is 180-200 mesh natural flake graphite powder.

[0008] Preferably, the carbon black particle size in step one is 5-20 μm.

[0009] Preferably, the modified alumina whisker composite reinforcing material in step one is prepared by the following steps: S1. Add alumina whiskers to an ethanol solution, ultrasonically disperse for 20-40 min, add hydrochloric acid solution to adjust the pH to 3-4, and stir at 50-60℃ for 2-3 h to obtain activated alumina whisker dispersion; S2. Dissolve tetrabutyl titanate in anhydrous ethanol, add it dropwise to the activated alumina whisker dispersion, stir at 50-60℃ for 3-5 h, centrifuge, wash, and dry to obtain titanium dioxide modified alumina whiskers. S3. Place the titanium dioxide-modified alumina whiskers in a tube furnace and heat them to 1000-1100°C under an argon protective atmosphere. Then, introduce a mixture of methane and H2 / Ar and keep the temperature for 1-3 hours. After the reaction is complete, turn off the methane and cool to room temperature under an argon protective atmosphere to obtain titanium carbide-modified alumina whiskers. S4. Add the titanium carbide modified alumina whiskers to an ethanol solution, add glacial acetic acid to adjust the pH to 4-5, add γ-glycidyl etheroxypropyltrimethoxysilane, react at 40-50℃ for 1-2 hours, centrifuge, wash, dry, mix with polyphenylene sulfide, melt blend, extrude and granulate, cool to room temperature to obtain the modified alumina whisker composite reinforcing material.

[0010] Preferably, the mass ratio of alumina whiskers to ethanol solution in S1 is 1:(10-20).

[0011] Preferably, the ethanol solution in S1 is an aqueous ethanol solution, and the volume ratio of ethanol to water is (3-5):1.

[0012] Preferably, the hydrochloric acid solution in S1 is an aqueous hydrochloric acid solution with a concentration of 0.1-0.3 mol / L.

[0013] Preferably, the mass ratio of tetrabutyl titanate, anhydrous ethanol, and activated alumina whisker dispersion in S2 is (20-30):(400-500):100.

[0014] Preferably, during the centrifugation process in S2, the centrifugation speed is 6000-8000 r / min and the centrifugation time is 5-10 min.

[0015] Preferably, the washing in step S2 involves washing twice with anhydrous ethanol.

[0016] Preferably, in the drying process of S2, the drying temperature is 60-80℃ and the drying time is 12-24h.

[0017] Preferably, during the heating process in S3, the heating rate is 5-10℃ / min.

[0018] Preferably, during the process of introducing the methane and H2 / Ar mixture in S3, the methane gas flow rate is 80-120 sccm, and the H2 / Ar mixture flow rate is 240-280 sccm.

[0019] Preferably, the ethanol solution in S4 is an aqueous ethanol solution, and the volume ratio of ethanol to water is (3-5):1.

[0020] Preferably, the mass ratio of titanium carbide-modified alumina whiskers, ethanol solution, γ-glycidyl etheroxypropyltrimethoxysilane, and polyphenylene sulfide in S4 is 100:(500-600):(2-4):(100-120).

[0021] Preferably, during the centrifugation process in S4, the centrifugation speed is 6000-8000 r / min and the centrifugation time is 5-10 min.

[0022] Preferably, the washing in step S4 involves washing twice with anhydrous ethanol.

[0023] Preferably, in the drying process of S4, the drying temperature is 60-80℃ and the drying time is 12-24h.

[0024] Preferably, during the melt blending process in S4, the temperature is 290-310℃ and the time is 2-5 minutes.

[0025] Preferably, the antioxidant in step one is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0026] Preferably, the dispersant in step one is polyethylene wax.

[0027] Preferably, in the melt blending process of step one, the main rotor speed of the twin-screw extruder is 30-50 r / min, the feed speed is 20-30 r / min, the melt blending temperature is 290-310℃, and the time is 2-5 min.

[0028] Preferably, in the hot pressing process of step one, the temperature is 290-310℃, the pressure is 10-30MPa, and the time is 15-30min.

[0029] Preferably, the thickness of the composite bipolar substrate in step one is 0.5-2 mm.

[0030] Preferably, in step one, the mass ratio of natural flake graphite, carbon black, polyphenylene sulfide resin, modified alumina whisker composite reinforcing material, antioxidant, polyphenylene sulfide grafted maleic anhydride, and dispersant is 100:(10-20):(40-50):(15-25):(0.2-0.5):(5-8):(0.5-2).

[0031] Preferably, the modified polyaniline conductive material in step two is prepared by the following steps: Step (1): Add aniline, 3,6-diaminocarbazole and 2-aminobenzothiazole to hydrochloric acid solution and disperse by ultrasonication for 20-40 min to obtain a dispersion. Step (2): Add ammonium persulfate to hydrochloric acid solution, stir to dissolve, and obtain oxidant solution; under ice-water bath conditions, add the oxidant solution dropwise to the dispersion, react for 20-24 hours, filter, wash, and dry to obtain modified polyaniline conductive material.

[0032] Preferably, the hydrochloric acid solution in step (1) is an aqueous hydrochloric acid solution with a concentration of 0.5-1.5 mol / L.

[0033] Preferably, in step (1), the mass ratio of aniline, 3,6-diaminocarbazole, 2-aminobenzothiazole, and hydrochloric acid solution is 100:(4-6):(3-6):(500-600).

[0034] Preferably, the hydrochloric acid solution in step (2) is an aqueous hydrochloric acid solution with a concentration of 0.5-1.5 mol / L.

[0035] Preferably, the temperature of the ice-water bath in step (2) is 0-5℃.

[0036] Preferably, in step (2), the mass ratio of ammonium persulfate, hydrochloric acid solution, and dispersion is (8-12):(100-200):100.

[0037] Preferably, in step (2), the washing is performed 2-3 times with a 0.1-0.5 mol / L hydrochloric acid solution, followed by rinsing once with deionized water.

[0038] Preferably, in step (2), the drying temperature is 60-80℃ and the drying time is 12-24h.

[0039] Preferably, the adhesive used in step two is polyvinylidene fluoride.

[0040] Preferably, in step two, the mass ratio of modified polyaniline conductive material, N-methylpyrrolidone, and binder is 100:(180-220):(8-12).

[0041] Preferably, in step two, the thickness of the conductive anti-corrosion coating is 20-40 μm.

[0042] Preferably, in step two, the drying temperature is 120-140℃ and the drying time is 4-8 hours.

[0043] Preferably, the positive electrode lead paste in step three is prepared by the following steps: adding lead powder, red lead, graphite powder, and glass short fibers into a paste mixer and mixing them evenly, adding deionized water and continuing to stir, and then slowly adding sulfuric acid solution to obtain the positive electrode lead paste.

[0044] Preferably, in the preparation method of the positive electrode lead paste, the length of the glass short fibers is 2.5-3 mm.

[0045] Preferably, in the preparation method of the positive electrode lead paste, the mass ratio of lead powder, red lead, graphite powder, glass short fiber, deionized water and sulfuric acid solution is 100: (10-20): (0.5-2): (0.05-0.2): (8-12): (5-10).

[0046] Preferably, in the method for preparing the positive electrode lead paste, the sulfuric acid solution is an aqueous sulfuric acid solution with a concentration of 30%-40%.

[0047] Preferably, the negative electrode lead paste in step three is prepared by the following steps: adding lead powder, barium sulfate, lignin, humic acid and glass short fibers into a paste mixer and mixing them evenly, adding deionized water and continuing to stir, and then slowly adding sulfuric acid solution to obtain negative electrode lead paste.

[0048] Preferably, in the preparation method of the negative electrode lead paste, the length of the glass short fibers is 2.5-3 mm.

[0049] Preferably, in the preparation method of the negative electrode lead paste, the mass ratio of lead powder, barium sulfate, lignin, humic acid, glass short fiber, deionized water and sulfuric acid solution is 100: (0.5-2): (0.1-0.5): (0.1-0.5): (0.05-0.2): (8-12): (5-10).

[0050] Preferably, in the method for preparing the negative electrode lead paste, the sulfuric acid solution is an aqueous sulfuric acid solution with a concentration of 30%-40%.

[0051] Preferably, in step three, the coating thickness of the positive electrode lead paste is 0.5-1.5 mm.

[0052] Preferably, in step three, the coating thickness of the negative electrode lead paste is 0.5-1.5 mm.

[0053] Preferably, the sulfuric acid solution in step three is a 30%-35% aqueous sulfuric acid solution.

[0054] Preferably, in step three, the curing process involves a curing temperature of 55°C, a humidity of 95%, and a curing time of 68 hours.

[0055] (iii) Beneficial technical effects Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses modified alumina whisker composite reinforcement material as the bipolar plate reinforcement component. Alumina whiskers have excellent heat resistance and mechanical strength, and can be used as a reinforcing skeleton to improve the mechanical properties and structural stability of composite materials. First, the system is adjusted to acidity using hydrochloric acid solution to fully protonate the hydroxyl groups on the surface of alumina whiskers, thereby improving the reactivity of the whisker surface. Tetrabutyl titanate is introduced into the activated alumina whisker dispersion system, and a hydrolysis-condensation reaction occurs in an alcohol solution environment. The generated titanium dioxide component is uniformly loaded on the surface of alumina whiskers, forming titanium dioxide-modified alumina whiskers. This provides a uniformly distributed titanium source for the subsequent carbonization reaction, and at the same time, it can increase the number of active sites on the surface of alumina whiskers, so that the titanium carbide structure can be formed in situ on the whisker surface, enhancing the interfacial bonding strength and avoiding the agglomeration and weak bonding problems common to external reinforcements. Then, high-temperature carbonization treatment is carried out. Under the action of a reducing atmosphere, titanium dioxide gradually transforms into a titanium carbide structure, so that a conductive titanium carbide modification layer is constructed on the surface of alumina whiskers. Titanium carbide possesses high electrical conductivity, corrosion resistance, and high thermal stability, which can improve the charge transport capacity of alumina whisker surfaces and enhance the conductivity of the reinforcing material. Furthermore, the introduction of the titanium carbide modification layer increases the interfacial contact opportunities between the whiskers and the conductive filler, facilitating the construction of conductive pathways within the composite material. Methane gas serves as the carbon source; H2 can regulate the methane cracking rate and inhibit excessive deposition of amorphous carbon, while Ar acts as a dilution gas, adjusting the partial pressure of reactants in the reaction atmosphere, which is beneficial for uniform titanium carbide deposition. Subsequently, the titanium carbide-modified alumina whiskers are surface-treated with γ-glycidoxypropyltrimethoxysilane, forming an organosilane bonding layer on the whisker surface. Simultaneously, the organic functional groups in γ-glycidoxypropyltrimethoxysilane can improve the interfacial bonding ability between the reinforcing material and polyphenylene sulfide resin, reducing whisker agglomeration. Surface-modified titanium carbide-modified alumina whiskers are melt-blended with polyphenylene sulfide (PPS), allowing PPS to uniformly coat the surface of the reinforcing material, forming a modified alumina whisker composite reinforcing material with good dispersibility and interfacial bonding. When this reinforcing material is added to a bipolar plate system, the synergistic effect of alumina whisker reinforcement, titanium carbide conductivity, silane interface regulation, and PPS chemical stabilization improves the mechanical strength, conductivity, and long-term corrosion resistance of the bipolar plate.

[0056] (2) This invention uses aniline, 3,6-diaminocarbazole, and 2-aminobenzothiazole to construct a modified polyaniline conductive material. Polyaniline, with its high conductivity and good electrochemical stability, is the main component for constructing the conductive network. 3,6-diaminocarbazole has a conjugated aromatic structure, and its introduction can improve electron delocalization capability. 2-Aminobenzothiazole contains nitrogen and sulfur heteroatoms, which can improve the composite material's tolerance to acidic environments. In an acidic environment, aniline-3,6-diaminocarbazole-2-aminobenzothiazole copolymer conductive material is prepared by ammonium persulfate oxidative polymerization. Hydrochloric acid solution, on the one hand, promotes the protonation of nitrogen-containing aromatic monomers such as aniline, increasing water solubility and improving the dispersion stability of the monomers in the reaction system; on the other hand, it can embed into the polyaniline backbone to form a polaron / bipolar delocalized structure, maintaining high conductivity of the polyaniline chain segments. During the oxidative polymerization process, the aniline monomer is first oxidized and polymerized by ammonium persulfate under acidic conditions to form a polyaniline backbone with a π-electron conjugated structure, providing the conductive basis for the material. Under oxidative conditions, 3,6-diaminocarbazole can generate nitrogen-centered or cationic free radicals, which can undergo CN or CC coupling with active sites on the polyaniline chain. This allows the carbazole structure to embed into polyaniline, inhibiting chain rearrangement, reducing defect states, and improving charge jumping efficiency, thereby constructing a multidimensional conductive pathway and enhancing conductivity and electrochemical stability. The aromatic amine groups of 2-aminobenzothiazole can form active intermediates such as free radical cations under oxidative conditions, embedding into the polyaniline conjugated backbone through copolymerization or side-chain doping mechanisms, thus participating in the construction of the conductive system. The N and S atoms in the benzothiazole ring can serve as electronic interaction sites, forming hydrogen bonds and π-π stacking with the imine, amine nitrogen, and conjugated backbone of polyaniline, thereby enhancing interfacial bonding, optimizing microphase separation, and improving the dispersion stability of conductive components. Simultaneously, the N and S heteroatoms can enhance the adsorption and barrier effect of corrosive ions in acidic electrolytes, reducing the diffusion of corrosive media into the material interior, slowing down interfacial oxidation degradation and conductive particle shedding, and improving the long-term service stability of the bipolar plate. Furthermore, the electronic interaction between the amino group and benzothiazole is beneficial for maintaining the stability of electron transport in the polymer system. By controlling the reaction temperature through low-temperature oxidative polymerization under ice-water bath conditions, the oxidative polymerization rate can be reduced, minimizing excessive cross-linking of chain segments and structural defects, thus improving the molecular structural uniformity of the copolymer conductive material. Subsequent acid washing removes unreacted monomer impurities and byproducts while maintaining the protonated state of polyaniline, which is beneficial for obtaining modified polyaniline conductive materials with high conductivity and stability. When this material is applied as a surface conductive and anti-corrosion coating to the substrate surface, it forms a surface transition layer with conductive and anti-corrosion functions, improving the electron transport capability of the bipolar plate surface while blocking acidic electrolyte corrosion.

[0057] (3) In the composite bipolar plate system, natural flake graphite serves as the main conductive component. Its layered structure provides a large electron transport interface, constructing a basic conductive path. Carbon black fills between the graphite layers, improving the contact state between fillers and enhancing the continuity of the conductive path. Polyphenylene sulfide resin, as the matrix material, possesses excellent acid resistance, heat resistance, and dimensional stability, providing stable support for conductive fillers and reinforcing materials, and improving the long-term stability of the composite substrate in acidic environments. Based on this, modified alumina whisker composite reinforcing material is introduced, where alumina whiskers play a reinforcing role, improving the mechanical strength of the composite bipolar substrate. The titanium carbide modification layer has good conductivity and corrosion resistance, improving the interfacial contact state between the reinforcing phase and the carbon-based conductive filler, promoting electron transport within the composite bipolar substrate, and enhancing the synergistic effect between the reinforcing phase and the conductive network. Furthermore, the silane structure on the surface of the modified alumina whiskers can improve its interfacial bonding ability with polyphenylene sulfide resin, reduce the agglomeration of reinforcing materials in the matrix, reduce structural defects caused by interfacial mismatch, and thus improve the mechanical stability of the composite substrate. Furthermore, a modified polyaniline conductive and anti-corrosion coating is applied to both sides of the composite bipolar substrate. The conjugated structure in the modified polyaniline provides a stable electron transport path and can generate π-π interactions with components such as graphite and carbon black, improving the interfacial bonding strength between the coating and the substrate, thus forming a continuous electron transport interface between the surface coating and the internal conductive system. Simultaneously, the 3,6-diaminocarbazole structure enhances the stability of the polyaniline conjugated system and improves the conductivity retention of the coating; the N and S heteroatoms in 2-aminobenzothiazole enhance the adsorption and barrier effect of the coating on corrosive media in acidic electrolytes, reducing the penetration of corrosive ions into the composite substrate and improving the corrosion resistance of the bipolar plate. Subsequently, positive and negative electrode lead pastes are applied to both sides of the modified composite bipolar substrate, giving the composite bipolar substrate both positive and negative electrode active functions, forming a bipolar plate structure for bipolar lead-acid batteries. The red lead in the positive electrode lead paste promotes the formation of positive electrode active materials, graphite powder helps improve the conductivity of the positive electrode layer, and short glass fibers enhance the structural stability of the active layer. The barium sulfate, lignin, and humic acid components in the negative electrode lead paste can improve the structure of the negative electrode active material and enhance cycle stability. Impregnation with sulfuric acid solution promotes the pre-sulfatation reaction within the lead paste, which is beneficial for forming a stable active material structure. Further, constant temperature and humidity curing ensures a stable bond between the lead paste layer and the composite bipolar substrate, improving the overall structural strength and electrochemical stability of the bipolar plate. Through the synergistic effect of the internal composite conductive reinforcing substrate, the surface-modified polyaniline conductive anti-corrosion coating, and the active layers of lead paste on both sides, the internal resistance of the bipolar plate is reduced, improving its acid corrosion resistance and long-term service stability.

[0058] (4) The composite material system constructed in this invention takes into account the stability of the conductive network, the load-bearing capacity of the enhanced phase and the corrosion resistance of the interface. While ensuring the mechanical strength and structural stability of the bipolar plate, it improves the conductivity, corrosion resistance and long-term service reliability of the material, which can meet the application requirements of bipolar plates in complex electrochemical environments. Detailed Implementation

[0059] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0060] Example 1 A method for preparing a highly conductive and corrosion-resistant composite material bipolar plate includes the following steps: Step 1: 100 parts of 180-mesh natural flake graphite, 10 parts of carbon black with a particle size of 5μm, 40 parts of polyphenylene sulfide resin, 15 parts of modified alumina whisker composite reinforcing material, 0.2 parts of antioxidant, 5 parts of polyphenylene sulfide grafted maleic anhydride, and 0.5 parts of dispersant polyethylene wax are added to a mixer and mixed. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain composite substrate granules. The main motor speed of the twin-screw extruder is 30 r / min, the feed speed is 20 r / min, the melt-blending temperature is 290℃, and the time is 5 min. The composite substrate granules are then placed in a mold and hot-pressed at 290℃ and 10MPa for 30 min. After demolding, a composite bipolar substrate with a thickness of 0.5 mm is obtained. Step 2: Add 100 parts of modified polyaniline conductive material to 180 parts of N-methylpyrrolidone, ultrasonically disperse for 20 min, then add 8 parts of binder polyvinylidene fluoride, mix evenly to obtain a conductive and anti-corrosion slurry, uniformly coat the conductive and anti-corrosion slurry on both sides of the composite bipolar substrate to obtain a conductive and anti-corrosion coating with a thickness of 20 μm, and dry at 120℃ for 8 h to obtain the modified composite bipolar substrate; Step 3: Apply positive electrode lead paste to one side of the modified composite bipolar substrate with a coating thickness of 0.5 mm, and apply negative electrode lead paste to the other side of the modified composite bipolar substrate with a coating thickness of 0.5 mm. After impregnation treatment with 30% sulfuric acid aqueous solution, place it in a constant temperature and humidity chamber for curing. The curing temperature is 55℃, the humidity is 95%, and the time is 68 hours to obtain a highly conductive and corrosion-resistant composite material bipolar plate.

[0061] In this embodiment, the preparation method of the modified alumina whisker composite reinforced material includes the following steps: S1. Prepare an ethanol solution by mixing 3 parts ethanol with 1 part deionized water. Add 1 part alumina whiskers to 10 parts ethanol solution, sonicate for 20 min, add 0.1 mol / L hydrochloric acid solution to adjust the pH to 3, and stir at 50℃ for 3 h to obtain activated alumina whisker dispersion. S2. Dissolve 20 parts of tetrabutyl titanate in 400 parts of anhydrous ethanol, add dropwise to 100 parts of the activated alumina whisker dispersion, stir at 50°C for 5 h, centrifuge at 6000 r / min for 10 min, wash twice with anhydrous ethanol, and dry at 60°C for 24 h to obtain titanium dioxide modified alumina whiskers. S3. The titanium dioxide-modified alumina whiskers are placed in a tube furnace and heated to 1000°C at a heating rate of 5°C / min under an argon protective atmosphere. Then, a mixture of methane and H2 / Ar is introduced and kept at this temperature for 3 hours. The flow rate of methane is 80 sccm and the flow rate of H2 / Ar is 240 sccm. After the reaction is completed, the methane is turned off and the mixture is cooled to room temperature under an argon protective atmosphere to obtain titanium carbide-modified alumina whiskers. S4. Add 100 parts of the titanium carbide modified alumina whiskers to 500 parts of ethanol solution, adjust the pH to 4 by adding glacial acetic acid, add 2 parts of γ-glycidyl etheroxypropyltrimethoxysilane, react at 40℃ for 2h, centrifuge at 6000r / min for 10min, wash twice with anhydrous ethanol, dry at 60℃ for 24h, mix with 100 parts of polyphenylene sulfide, melt blend, extrude granulate, cool to room temperature to obtain modified alumina whisker composite reinforcing material, wherein the melt blending temperature is 290℃ and the time is 5min.

[0062] In this embodiment, the preparation method of the modified polyaniline conductive material includes the following steps: Step (1): Add 100 parts of aniline, 4 parts of 3,6-diaminocarbazole and 3 parts of 2-aminobenzothiazole to 500 parts of 0.5 mol / L hydrochloric acid solution and sonicate for 20 min to obtain a dispersion. Step (2): Add 8 parts of ammonium persulfate to 100 parts of hydrochloric acid solution with a concentration of 0.5 mol / L, stir to dissolve, and obtain an oxidant solution; under 0℃ ice-water bath conditions, add the oxidant solution dropwise to 100 parts of the dispersion, react for 20 h, filter, wash twice with 0.1 mol / L hydrochloric acid solution, rinse once with deionized water, and dry at 60℃ for 24 h to obtain modified polyaniline conductive material.

[0063] In this embodiment, the preparation method of the positive electrode lead paste includes the following steps: 100 parts of lead powder, 10 parts of red lead, 0.5 parts of graphite powder, and 0.05 parts of glass short fibers with a length of 2.5 mm are added to a paste mixer and mixed evenly. 8 parts of deionized water are added and stirring is continued. Then, 5 parts of sulfuric acid solution with a concentration of 30% are slowly added to obtain the positive electrode lead paste.

[0064] In this embodiment, the preparation method of negative electrode lead paste includes the following steps: 100 parts of lead powder, 0.5 parts of barium sulfate, 0.1 parts of lignin, 0.1 parts of humic acid, and 0.05 parts of glass short fibers with a length of 2.5 mm are added to a paste mixer and mixed evenly. 8 parts of deionized water are added and stirring is continued. Then, 5 parts of sulfuric acid solution with a concentration of 30% are slowly added to obtain negative electrode lead paste.

[0065] Example 2 A method for preparing a highly conductive and corrosion-resistant composite material bipolar plate includes the following steps: Step 1: 100 parts of 185-mesh natural flake graphite, 13 parts of carbon black with a particle size of 10 μm, 43 parts of polyphenylene sulfide resin, 18 parts of modified alumina whisker composite reinforcing material, 0.3 parts of antioxidant, 6 parts of polyphenylene sulfide grafted maleic anhydride, and 1 part of dispersant polyethylene wax are added to a mixer and mixed. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain composite substrate granules. The main motor speed of the twin-screw extruder is 35 r / min, the feed speed is 23 r / min, the melt-blending temperature is 295℃, and the time is 4 min. The composite substrate granules are then placed in a mold and hot-pressed at 295℃ and 15 MPa for 25 min. After demolding, a composite bipolar substrate with a thickness of 1 mm is obtained. Step 2: Add 100 parts of modified polyaniline conductive material to 190 parts of N-methylpyrrolidone, ultrasonically disperse for 25 min, then add 9 parts of binder polyvinylidene fluoride, mix evenly to obtain a conductive and anti-corrosion slurry, uniformly coat the conductive and anti-corrosion slurry on both sides of the composite bipolar substrate to obtain a conductive and anti-corrosion coating with a thickness of 25 μm, and dry at 125℃ for 7 h to obtain the modified composite bipolar substrate; Step 3: Apply positive electrode lead paste to one side of the modified composite bipolar substrate with a coating thickness of 0.8 mm, and apply negative electrode lead paste to the other side of the modified composite bipolar substrate with a coating thickness of 0.8 mm. After impregnation treatment with 32% sulfuric acid aqueous solution, place it in a constant temperature and humidity chamber for curing. The curing temperature is 55℃, the humidity is 95%, and the time is 68 hours to obtain a highly conductive and corrosion-resistant composite material bipolar plate.

[0066] In this embodiment, the preparation method of the modified alumina whisker composite reinforced material includes the following steps: S1. Prepare an ethanol solution by mixing 3.5 parts of ethanol with 1 part of deionized water. Add 1 part of alumina whiskers to 13 parts of ethanol solution, sonicate for 25 min, add 0.15 mol / L hydrochloric acid solution to adjust the pH to 3.3, and stir at 53℃ for 2.7 h to obtain activated alumina whisker dispersion. S2. Dissolve 23 parts of tetrabutyl titanate in 425 parts of anhydrous ethanol, add dropwise to 100 parts of the activated alumina whisker dispersion, stir at 53°C for 4.5 h, centrifuge at 6500 r / min for 8 min, wash twice with anhydrous ethanol, and dry at 65°C for 20 h to obtain titanium dioxide modified alumina whiskers. S3. The titanium dioxide-modified alumina whiskers are placed in a tube furnace and heated to 1025°C at a heating rate of 7°C / min under an argon protective atmosphere. Then, a mixture of methane and H2 / Ar is introduced and held at this temperature for 2.5 hours. The flow rate of methane is 90 sccm and the flow rate of H2 / Ar is 250 sccm. After the reaction is completed, the methane is turned off and the mixture is cooled to room temperature under an argon protective atmosphere to obtain titanium carbide-modified alumina whiskers. S4. Add 100 parts of the titanium carbide modified alumina whiskers to 525 parts of ethanol solution, adjust the pH to 4.3 by adding glacial acetic acid, add 2.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, react at 43℃ for 1.7h, centrifuge at 6500r / min for 8min, wash twice with anhydrous ethanol, dry at 65℃ for 20h, mix with 105 parts of polyphenylene sulfide, melt blend, extrude granulate, cool to room temperature to obtain modified alumina whisker composite reinforcing material, wherein the melt blending temperature is 295℃ and the time is 4min.

[0067] In this embodiment, the preparation method of the modified polyaniline conductive material includes the following steps: Step (1): Add 100 parts of aniline, 4.5 parts of 3,6-diaminocarbazole and 4 parts of 2-aminobenzothiazole to 525 parts of hydrochloric acid solution with a concentration of 0.8 mol / L, and sonicate for 25 min to obtain a dispersion. Step (2): Add 9 parts of ammonium persulfate to 125 parts of hydrochloric acid solution with a concentration of 0.8 mol / L, stir to dissolve, and obtain an oxidant solution; under the condition of ice-water bath at 2℃, add the oxidant solution dropwise to 100 parts of the dispersion, react for 21 h, filter, wash twice with 0.2 mol / L hydrochloric acid solution, rinse once with deionized water, and dry at 65℃ for 20 h to obtain modified polyaniline conductive material.

[0068] In this embodiment, the preparation method of the positive electrode lead paste includes the following steps: 100 parts of lead powder, 13 parts of red lead, 1 part of graphite powder, and 0.1 parts of glass short fibers with a length of 2.7 mm are added to a paste mixer and mixed evenly. 9 parts of deionized water are added and stirring is continued. Then, 7 parts of sulfuric acid solution with a concentration of 33% are slowly added to obtain the positive electrode lead paste.

[0069] In this embodiment, the preparation method of negative electrode lead paste includes the following steps: 100 parts of lead powder, 1 part of barium sulfate, 0.2 parts of lignin, 0.2 parts of humic acid, and 0.1 parts of glass short fibers with a length of 2.7 mm are added to a paste mixer and mixed evenly. Then, 9 parts of deionized water are added and stirring is continued. Subsequently, 7 parts of sulfuric acid solution with a concentration of 33% are slowly added to obtain negative electrode lead paste.

[0070] Example 3 A method for preparing a highly conductive and corrosion-resistant composite material bipolar plate includes the following steps: Step 1: 100 parts of 195-mesh natural flake graphite, 17 parts of carbon black with a particle size of 15μm, 47 parts of polyphenylene sulfide resin, 22 parts of modified alumina whisker composite reinforcing material, 0.4 parts of antioxidant, 7 parts of polyphenylene sulfide grafted maleic anhydride, and 1.5 parts of dispersant polyethylene wax are added to a mixer and mixed. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain composite substrate granules. The main motor speed of the twin-screw extruder is 45 r / min, the feed speed is 27 r / min, the melt-blending temperature is 305℃, and the time is 3 min. The composite substrate granules are then placed in a mold and hot-pressed at 305℃ and 25MPa for 20 min. After demolding, a composite bipolar substrate with a thickness of 1.5 mm is obtained. Step 2: Add 100 parts of modified polyaniline conductive material to 210 parts of N-methylpyrrolidone, ultrasonically disperse for 35 min, then add 11 parts of binder polyvinylidene fluoride, mix evenly to obtain a conductive and anti-corrosion slurry, uniformly coat the conductive and anti-corrosion slurry on both sides of the composite bipolar substrate to obtain a conductive and anti-corrosion coating with a thickness of 35 μm, and dry at 135℃ for 5 h to obtain the modified composite bipolar substrate; Step 3: Apply positive electrode lead paste to one side of the modified composite bipolar substrate with a coating thickness of 1.2 mm, and apply negative electrode lead paste to the other side of the modified composite bipolar substrate with a coating thickness of 1.2 mm. After impregnation treatment with 33% sulfuric acid aqueous solution, place it in a constant temperature and humidity chamber for curing. The curing temperature is 55℃, the humidity is 95%, and the time is 68 hours to obtain a highly conductive and corrosion-resistant composite material bipolar plate.

[0071] In this embodiment, the preparation method of the modified alumina whisker composite reinforced material includes the following steps: S1. Prepare an ethanol solution by mixing 4.5 parts of ethanol with 1 part of deionized water. Add 1 part of alumina whiskers to 17 parts of ethanol solution, sonicate for 35 min, add 0.25 mol / L hydrochloric acid solution to adjust the pH to 3.7, and stir at 57℃ for 2.3 h to obtain activated alumina whisker dispersion. S2. Dissolve 27 parts of tetrabutyl titanate in 475 parts of anhydrous ethanol, add dropwise to 100 parts of the activated alumina whisker dispersion, stir at 57°C for 3.5 h, centrifuge at 7500 r / min for 7 min, wash twice with anhydrous ethanol, and dry at 75°C for 16 h to obtain titanium dioxide modified alumina whiskers. S3. The titanium dioxide-modified alumina whiskers are placed in a tube furnace and heated to 1075°C at a heating rate of 8°C / min under an argon protective atmosphere. Then, a mixture of methane and H2 / Ar is introduced and held at this temperature for 1.5 hours. The flow rate of methane is 110 sccm and the flow rate of H2 / Ar is 270 sccm. After the reaction is completed, the methane is turned off and the mixture is cooled to room temperature under an argon protective atmosphere to obtain titanium carbide-modified alumina whiskers. S4. Add 100 parts of the titanium carbide modified alumina whiskers to 575 parts of ethanol solution, adjust the pH to 4.7 by adding glacial acetic acid, add 3.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, react at 47℃ for 1.3h, centrifuge at 7500r / min for 7min, wash twice with anhydrous ethanol, dry at 75℃ for 16h, mix with 115 parts of polyphenylene sulfide, melt blend, extrude granulate, cool to room temperature to obtain modified alumina whisker composite reinforcing material, wherein the melt blending temperature is 305℃ and the time is 3min.

[0072] In this embodiment, the preparation method of the modified polyaniline conductive material includes the following steps: Step (1): Add 100 parts of aniline, 5.5 parts of 3,6-diaminocarbazole and 5 parts of 2-aminobenzothiazole to 575 parts of hydrochloric acid solution with a concentration of 1.2 mol / L, and sonicate for 35 min to obtain a dispersion. Step (2): Add 11 parts of ammonium persulfate to 175 parts of hydrochloric acid solution with a concentration of 1.2 mol / L, stir to dissolve, and obtain an oxidant solution; under the condition of ice-water bath at 3℃, add the oxidant solution dropwise to 100 parts of the dispersion, react for 23 h, filter, wash 3 times with 0.4 mol / L hydrochloric acid solution, rinse once with deionized water, and dry at 75℃ for 16 h to obtain modified polyaniline conductive material.

[0073] In this embodiment, the preparation method of the positive electrode lead paste includes the following steps: 100 parts of lead powder, 17 parts of red lead, 1.5 parts of graphite powder, and 0.15 parts of glass short fibers with a length of 2.8 mm are added to a paste mixer and mixed evenly. 11 parts of deionized water are added and stirring is continued. Then, 8 parts of sulfuric acid solution with a concentration of 37% are slowly added to obtain the positive electrode lead paste.

[0074] In this embodiment, the preparation method of negative electrode lead paste includes the following steps: 100 parts of lead powder, 1.5 parts of barium sulfate, 0.4 parts of lignin, 0.4 parts of humic acid, and 0.15 parts of glass short fibers with a length of 2.8 mm are added to a paste mixer and mixed evenly. 11 parts of deionized water are added and stirring is continued. Then, 8 parts of sulfuric acid solution with a concentration of 37% are slowly added to obtain negative electrode lead paste.

[0075] Example 4 A method for preparing a highly conductive and corrosion-resistant composite material bipolar plate includes the following steps: Step 1: 100 parts of 200-mesh natural flake graphite, 20 parts of carbon black with a particle size of 20μm, 50 parts of polyphenylene sulfide resin, 25 parts of modified alumina whisker composite reinforcing material, 0.5 parts of antioxidant, 8 parts of polyphenylene sulfide grafted maleic anhydride, and 2 parts of dispersant polyethylene wax are added to a mixer and mixed. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain composite substrate granules. The main motor speed of the twin-screw extruder is 50 r / min, the feed speed is 30 r / min, the melt-blending temperature is 310℃, and the time is 2 min. The composite substrate granules are then placed in a mold and hot-pressed at 310℃ and 30MPa for 15 min. After demolding, a composite bipolar substrate with a thickness of 2 mm is obtained. Step 2: Add 100 parts of modified polyaniline conductive material to 220 parts of N-methylpyrrolidone, ultrasonically disperse for 40 min, then add 12 parts of binder polyvinylidene fluoride, mix evenly to obtain a conductive and anti-corrosion slurry, uniformly coat the conductive and anti-corrosion slurry on both sides of the composite bipolar substrate to obtain a conductive and anti-corrosion coating with a thickness of 40 μm, and dry at 140℃ for 4 h to obtain the modified composite bipolar substrate; Step 3: Apply positive electrode lead paste to one side of the modified composite bipolar substrate with a coating thickness of 1.5 mm, and apply negative electrode lead paste to the other side of the modified composite bipolar substrate with a coating thickness of 1.5 mm. After impregnation treatment with 35% sulfuric acid aqueous solution, place it in a constant temperature and humidity chamber for curing. The curing temperature is 55℃, the humidity is 95%, and the time is 68 hours to obtain a highly conductive and corrosion-resistant composite material bipolar plate.

[0076] In this embodiment, the preparation method of the modified alumina whisker composite reinforced material includes the following steps: S1. Prepare an ethanol solution by mixing 5 parts ethanol with 1 part deionized water. Add 1 part alumina whiskers to 20 parts ethanol solution, sonicate for 40 min, add 0.3 mol / L hydrochloric acid solution to adjust the pH to 4, and stir at 60℃ for 2 h to obtain activated alumina whisker dispersion. S2. Dissolve 30 parts of tetrabutyl titanate in 500 parts of anhydrous ethanol, add dropwise to 100 parts of the activated alumina whisker dispersion, stir at 60°C for 3 hours, centrifuge at 8000 r / min for 5 minutes, wash twice with anhydrous ethanol, and dry at 80°C for 12 hours to obtain titanium dioxide modified alumina whiskers. S3. The titanium dioxide-modified alumina whiskers are placed in a tube furnace and heated to 1100°C at a heating rate of 10°C / min under an argon protective atmosphere. Then, a mixture of methane and H2 / Ar is introduced and kept at this temperature for 1 hour. The flow rate of methane is 120 sccm and the flow rate of H2 / Ar is 280 sccm. After the reaction is completed, the methane is turned off and the mixture is cooled to room temperature under an argon protective atmosphere to obtain titanium carbide-modified alumina whiskers. S4. Add 100 parts of the titanium carbide modified alumina whiskers to 600 parts of ethanol solution, adjust the pH to 5 by adding glacial acetic acid, add 4 parts of γ-glycidyl etheroxypropyltrimethoxysilane, react at 50°C for 1 h, centrifuge at 8000 r / min for 5 min, wash twice with anhydrous ethanol, dry at 80°C for 12 h, mix with 120 parts of polyphenylene sulfide, melt blend, extrude granulate, cool to room temperature, and obtain the modified alumina whisker composite reinforcing material. The melt blending temperature is 310°C and the time is 2 min.

[0077] In this embodiment, the preparation method of the modified polyaniline conductive material includes the following steps: Step (1): Add 100 parts of aniline, 6 parts of 3,6-diaminocarbazole and 6 parts of 2-aminobenzothiazole to 600 parts of hydrochloric acid solution with a concentration of 1.5 mol / L, and sonicate for 40 min to obtain a dispersion. Step (2): Add 12 parts of ammonium persulfate to 200 parts of hydrochloric acid solution with a concentration of 1.5 mol / L, stir to dissolve, and obtain an oxidant solution; under the condition of ice-water bath at 5℃, add the oxidant solution dropwise to 100 parts of the dispersion, react for 24 h, filter, wash 3 times with 0.5 mol / L hydrochloric acid solution, rinse once with deionized water, and dry at 80℃ for 12 h to obtain modified polyaniline conductive material.

[0078] In this embodiment, the preparation method of positive electrode lead paste includes the following steps: 100 parts of lead powder, 20 parts of red lead, 2 parts of graphite powder, and 0.2 parts of glass short fibers with a length of 3 mm are added to a paste mixer and mixed evenly. 12 parts of deionized water are added and stirring is continued. Then, 10 parts of sulfuric acid solution with a concentration of 40% are slowly added to obtain positive electrode lead paste.

[0079] In this embodiment, the preparation method of negative electrode lead paste includes the following steps: 100 parts of lead powder, 2 parts of barium sulfate, 0.5 parts of lignin, 0.5 parts of humic acid, and 0.2 parts of glass short fibers with a length of 3 mm are added to a paste mixer and mixed evenly. 12 parts of deionized water are added and stirring is continued. Then, 10 parts of sulfuric acid solution with a concentration of 40% are slowly added to obtain negative electrode lead paste.

[0080] Comparative Example 1 A method for preparing a highly conductive and corrosion-resistant composite bipolar plate, compared with Example 3, differs in that: in this comparative example, no modified alumina whisker composite reinforcing material is added in step one, while the other components and preparation methods are completely consistent with Example 3.

[0081] Comparative Example 2 A method for preparing a highly conductive and corrosion-resistant composite bipolar plate, compared with Example 3, differs in that: in this comparative example, the two sides of the composite bipolar substrate are not coated with conductive anti-corrosion slurry in step two, while the other components and preparation methods are completely consistent with Example 3.

[0082] Comparative Example 3 A method for preparing a highly conductive and corrosion-resistant composite bipolar plate, compared with Example 3, differs in that: in this comparative example, the modified alumina whisker composite reinforcing material in step one is replaced with an equal amount of alumina whiskers, while the other components and preparation methods are completely consistent with Example 3.

[0083] Comparative Example 4 A method for preparing a highly conductive and corrosion-resistant composite bipolar plate, compared with Example 3, differs in that: in this comparative example, the modified polyaniline conductive material in step two is replaced with an equal amount of polyaniline, while the other components and preparation methods are completely consistent with Example 3.

[0084] The modified composite bipolar substrates prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to relevant performance tests, and the test results are shown below: (1) Bending strength test: The three-point bending method was used to test the sample. The sample size was 80mm×10mm×2mm. The span of the universal testing machine was adjusted to 40mm and the loading speed was 1mm / min. The bending strength was calculated. (2) Conductivity test: Place the sample under the four probes, adjust the height of the four probes to make them contact the sample, and use a four-probe tester to test the conductivity of the bipolar substrate. (3) Corrosion resistance test: The corrosion resistance of the composite bipolar substrate was measured using an electrochemical workstation and a standard three-electrode unit. The bipolar substrate was set to have an area of ​​1 cm². 2 The sample was used as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum sheet as the auxiliary electrode for testing. The electrolyte solution was set to 0.5M H2SO4 solution at 80℃, the potential range was set to -0.6V to 1V, the scan rate was 1mV / s, and the corrosion potential and corrosion current density were tested. (4) Long-term service stability test: The bipolar substrate sample was immersed in 0.5M H2SO4 solution at 80℃ for 500h. After being taken out, it was rinsed with deionized water and dried at 60℃ to constant weight. The mass change before and after immersion was recorded and the mass loss rate was calculated. At the same time, the conductivity before and after immersion was tested and the conductivity retention rate was calculated. The test results are shown in Table 1: Table 1

[0085] As shown in Table 1, the modified composite bipolar substrates prepared in Examples 1-4 all exhibit superior electrical conductivity, corrosion resistance, and mechanical strength. Among them, Example 3 demonstrates the best overall performance, with a bending strength of 70.2 MPa, an electrical conductivity of 169.7 S / cm, a corrosion potential of 0.215 V, and a corrosion current density of 0.162 μA / cm. 2After 500 hours of acid immersion, the mass loss rate was 0.86%, and the conductivity retention rate was 97.2%. Compared with Example 3, Comparative Example 1 did not add modified alumina whisker composite reinforcement material, lacking the bridging reinforcement effect of whiskers and the conductivity and corrosion resistance contribution of the titanium carbide modification layer, resulting in a decrease in the material's bending strength, conductivity, corrosion resistance, and long-term stability. In Comparative Example 2, the composite bipolar substrate was not coated with conductive anti-corrosion slurry on both sides. The composite bipolar plate lacked conductive pathways constructed by conjugated polymers, and the interfacial contact between graphite and carbon black was insufficient, leading to an increase in electron transport impedance and a sharp decrease in conductivity. At the same time, the absence of 2-aminobenzothiazole reduced the overall corrosion resistance of the material, and the corrosion current density increased. In Comparative Example 3, the modified alumina whisker composite reinforcement material was replaced with an equal amount of alumina whiskers. Lacking a titanium carbide conductive modification layer, it could not participate in the construction of the conductive network. Furthermore, the lack of γ-glycidyl etheroxypropyltrimethoxysilane modification treatment resulted in poor interfacial compatibility between the whiskers and the polyphenylene sulfide resin matrix, leading to easy agglomeration and a slight decrease in the bipolar plate's flexural strength, conductivity, corrosion resistance, and long-term stability. In Comparative Example 4, the modified polyaniline conductive material was replaced with an equal amount of polyaniline. The lack of synergistic modification with carbazole and benzothiazole groups reduced the degree of conjugated structure optimization and decreased carrier transport paths. Simultaneously, the lack of heteroatom adsorption and blocking effects on acidic corrosive media led to a slight decrease in the bipolar plate's flexural strength, conductivity, corrosion resistance, and long-term stability.

[0086] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a highly conductive and corrosion-resistant composite bipolar plate, characterized in that: Includes the following steps: Step 1: Natural flake graphite, carbon black, polyphenylene sulfide resin, modified alumina whisker composite reinforcing material, antioxidant, polyphenylene sulfide grafted maleic anhydride, and dispersant are added to a mixer for mixing. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain composite substrate granules. The composite substrate granules are placed in a mold, hot-pressed, and demolded to obtain a composite bipolar substrate. Step 2: Add the modified polyaniline conductive material to N-methylpyrrolidone, ultrasonically disperse for 20-40 minutes, then add the binder and mix evenly to obtain a conductive and anti-corrosion slurry. Coat the conductive and anti-corrosion slurry evenly on both sides of the composite bipolar substrate and dry to obtain the modified composite bipolar substrate. Step 3: Apply positive lead paste to one side of the modified composite bipolar substrate and negative lead paste to the other side of the modified composite bipolar substrate. After being impregnated with sulfuric acid solution, the substrate is placed in a constant temperature and humidity chamber for curing to obtain a highly conductive and corrosion-resistant composite material bipolar plate. The modified alumina whisker composite reinforcing material in step one is prepared by the following steps: S1. Add alumina whiskers to an ethanol solution, ultrasonically disperse for 20-40 min, add hydrochloric acid solution to adjust the pH to 3-4, and stir at 50-60℃ for 2-3 h to obtain an activated alumina whisker dispersion, wherein the mass ratio of alumina whiskers to ethanol solution is 1:(10-20). S2. Dissolve tetrabutyl titanate in anhydrous ethanol and add it dropwise to the activated alumina whisker dispersion. Stir at 50-60℃ for 3-5 hours, centrifuge, wash, and dry to obtain titanium dioxide modified alumina whiskers. The mass ratio of tetrabutyl titanate, anhydrous ethanol, and activated alumina whisker dispersion is (20-30):(400-500):

100. S3. The titanium dioxide-modified alumina whiskers are placed in a tube furnace and heated to 1000-1100℃ under an argon protective atmosphere. Then, a mixture of methane and H2 / Ar is introduced and kept at this temperature for 1-3 hours. The flow rate of methane is 80-120 sccm and the flow rate of H2 / Ar is 240-280 sccm. After the reaction is completed, the methane is turned off and the mixture is cooled to room temperature under an argon protective atmosphere to obtain titanium carbide-modified alumina whiskers. S4. Add the titanium carbide-modified alumina whiskers to an ethanol solution, add glacial acetic acid to adjust the pH to 4-5, add γ-glycidyl oxypropyltrimethoxysilane, react at 40-50℃ for 1-2 hours, centrifuge, wash, dry, mix with polyphenylene sulfide, melt blend, extrude and granulate, cool to room temperature to obtain the modified alumina whisker composite reinforcing material, wherein the mass ratio of titanium carbide-modified alumina whiskers, ethanol solution, γ-glycidyl oxypropyltrimethoxysilane, and polyphenylene sulfide is 100:(500-600):(2-4):(100-120).

2. The method for preparing a highly conductive and corrosion-resistant composite bipolar plate according to claim 1, characterized in that: In step one, during the melt blending process, the main rotor speed of the twin-screw extruder is 30-50 r / min, the feed speed is 20-30 r / min, the melt blending temperature is 290-310℃, and the time is 2-5 min; during the hot pressing process, the temperature is 290-310℃, the pressure is 10-30 MPa, and the time is 15-30 min.

3. The method for preparing a highly conductive and corrosion-resistant composite bipolar plate according to claim 1, characterized in that: In step one, the mass ratio of natural flake graphite, carbon black, polyphenylene sulfide resin, modified alumina whisker composite reinforcing material, antioxidant, polyphenylene sulfide grafted maleic anhydride, and dispersant is 100:(10-20):(40-50):(15-25):(0.2-0.5):(5-8):(0.5-2).

4. The method for preparing a highly conductive and corrosion-resistant composite bipolar plate according to claim 1, characterized in that: The modified polyaniline conductive material in step two is prepared by the following steps: Step (1): Add aniline, 3,6-diaminocarbazole and 2-aminobenzothiazole to hydrochloric acid solution and ultrasonically disperse for 20-40 min to obtain a dispersion. The mass ratio of aniline, 3,6-diaminocarbazole, 2-aminobenzothiazole and hydrochloric acid solution is 100:(4-6):(3-6):(500-600). Step (2): Add ammonium persulfate to hydrochloric acid solution, stir to dissolve, and obtain oxidant solution; under ice-water bath conditions, add the oxidant solution dropwise to the dispersion, react for 20-24 hours, wherein the mass ratio of ammonium persulfate, hydrochloric acid solution and dispersion is (8-12):(100-200):100, filter, wash and dry to obtain modified polyaniline conductive material.

5. The method for preparing a highly conductive and corrosion-resistant composite bipolar plate according to claim 1, characterized in that: In step two, the mass ratio of modified polyaniline conductive material, N-methylpyrrolidone, and binder is 100:(180-220):(8-12).

6. The method for preparing a highly conductive and corrosion-resistant composite material bipolar plate according to claim 1, characterized in that: The preparation method of the positive electrode lead paste in step three includes the following steps: adding lead powder, red lead, graphite powder, and glass short fibers into a paste mixer and mixing them evenly, adding deionized water and continuing to stir, and then slowly adding sulfuric acid solution to obtain positive electrode lead paste. The mass ratio of lead powder, red lead, graphite powder, glass short fibers, deionized water, and sulfuric acid solution is 100:(10-20):(0.5-2):(0.05-0.2):(8-12):(5-10).

7. The method for preparing a highly conductive and corrosion-resistant composite bipolar plate according to claim 1, characterized in that: The negative electrode lead paste in step three is prepared by the following steps: adding lead powder, barium sulfate, lignin, humic acid, and glass short fibers into a paste mixer and mixing them evenly, adding deionized water and continuing to stir, and then slowly adding sulfuric acid solution to obtain negative electrode lead paste. The mass ratio of lead powder, barium sulfate, lignin, humic acid, glass short fibers, deionized water, and sulfuric acid solution is 100:(0.5-2):(0.1-0.5):(0.1-0.5):(0.05-0.2):(8-12):(5-10).

8. The method for preparing a highly conductive and corrosion-resistant composite bipolar plate according to claim 1, characterized in that: In step three, the curing process is carried out at a temperature of 55°C, a humidity of 95%, and a time of 68 hours.

9. A highly conductive and corrosion-resistant composite material bipolar plate, characterized in that: It is prepared by the method for preparing a highly conductive and corrosion-resistant composite material bipolar plate according to any one of claims 1-8.

Citation Information

Patent Citations

  • Modified expanded graphite based composite material bipolar plate and preparation method thereof

    CN103633340A

  • Novel metal graphite composite bipolar plate and preparation method thereof

    CN115566202A